2017
DOI: 10.1177/0310057x1704500207
|View full text |Cite
|
Sign up to set email alerts
|

The Tracheal Accordion and the Position of the Endotracheal Tube

Abstract: The purpose of this review is to, first, determine the static factors that affect the length of the human trachea across different populations and, second, to investigate whether or not there are dynamic factors that cause the length of the human trachea to vary within the same individual. We also investigated whether these changes in tracheal length within the same individual are significant enough to increase the risk of endobronchial intubation or accidental extubation. A PubMed/MEDLINE and a Web of Science… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 72 publications
4
23
0
Order By: Relevance
“…For the prevention of deep tube malposition, the recommended insertion depths of tracheal tubes for achieving an acceptable TCD are 20-21 cm in women and 22-23 cm in men, although special circumstances (head and neck movements during interventions) and stature (eg, short neck anatomy) always require individual considerations. 16 22 23 Although we did not document tube insertion lengths at ED admission in the current study, we recommend its documentation in the charts. Moreover, a standardised assessment including all relevant parameters of emergency airway management is strongly recommended in order to provide comparability in future studies.…”
Section: Avoidable Tube Thoracostomymentioning
confidence: 88%
“…For the prevention of deep tube malposition, the recommended insertion depths of tracheal tubes for achieving an acceptable TCD are 20-21 cm in women and 22-23 cm in men, although special circumstances (head and neck movements during interventions) and stature (eg, short neck anatomy) always require individual considerations. 16 22 23 Although we did not document tube insertion lengths at ED admission in the current study, we recommend its documentation in the charts. Moreover, a standardised assessment including all relevant parameters of emergency airway management is strongly recommended in order to provide comparability in future studies.…”
Section: Avoidable Tube Thoracostomymentioning
confidence: 88%
“…Then, Lal et al, (11)'s study found a correlation between ETT depth and This work is licensed under a Creative Commons Attribution-ShareAlike 4.0 International License height related to gender, yet it was not significant except in some extreme cases. Herway et al, (12) found a length difference of trachea, namely 0.7 cm longer for men. Research conducted by Fatma, (13) on body anthropometry found that men have a higher body posture than women.…”
Section: Resultsmentioning
confidence: 92%
“…Cardiac and pulmonary diseases may cause changes in tracheal anatomy, as well as goiter, smoking and aging [1,3]. In addition to anatomical changes, there are dynamic changes of the tracheal following anesthesia and relaxation [4]. Tracheal anatomy has great importance in procedures as tracheal intubation and ventilation [5,6].…”
Section: Introductionmentioning
confidence: 99%